Unveiling the Antioxidant Therapeutic Functionality of Sustainable Olive Pomace Active Ingredients - Javier Quero; Lina F. Ballesteros; Pedro Ferreira-Santos; Gustavo R. Velderrain-Rodriguez; Cristina M. R. Rocha; Ricardo N. Pereira; José A. Teixeira; Olga Martin-Belloso; Jesús Osada; María Jesús Rodríguez-Yoldi (MDPI AG, 2022)
Olive pomace (OP) is the main residue that results from olive oil production. OP is rich in bioactive compounds, including polyphenols, so its use in the treatments of diseases related to oxidative stress, such as cancer, could be considered. The present work aimed to study the biological properties of different OP extracts, obtained by ohmic heating-assisted extraction and conventional heating, using water and 50% ethanol, in the treatment and prevention of colorectal cancer through Caco-2 cell models. Additionally, an in-silico analysis was performed to identify the phenolic intestinal absorption and Caco-2 permeability. The extracts were chemically characterized, and it was found that the Ohmic-hydroethanolic (OH-EtOH) extract had the highest antiproliferative effect, probably due to its higher content of phenolic compounds. The OH-EtOH induced potential modifications in the mitochondrial membrane and led to apoptosis by cell cycle arrest in the G1/S phases with activation of p53 and caspase 3 proteins. In addition, this extract protected the intestine against oxidative stress (ROS) caused by H2O2. Therefore, the bioactive compounds present in OP and recovered by applying a green technology such as ohmic-heating, show promising potential to be used in food, nutraceutical, and biomedical applications, reducing this waste and facilitating the circular economy.